2005
DOI: 10.1021/jf048541l
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stage of Maturity and Cooking on the Chemical Composition of Select Mushroom Varieties

Abstract: Select mushrooms were analyzed for proximate constituents and carbohydrate profiles either raw or cooked and at different stages of maturity. White button mushrooms (Agaricus biporus) contained high concentrations of ash (12.5 and 11.9% for immature and mature mushrooms, respectively). Starch and total dietary fiber (TDF) concentrations were higher in maitake (Grifola frondosa) and shiitake (Lentinus edodes) mushrooms. Crude protein (CP) and acid-hydrolyzed fat (AHF) were highest in crimini (Agaricus bisporus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
5
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 33 publications
9
62
5
1
Order By: Relevance
“…Fe and Zn deficiency in particular appears to be a global health issue, affecting the populations of both developed and undeveloped countries [58]. Our finding highlights the nutritional value of G. frondosa which was previously shown to contain high concentrations of starch and total dietary fiber [59]. Although the bioavailability of Ca, Cu, Fe, Mg, Mn, P and Zn in G. frondosa remains to be studied more fully, this species would appear to be a promising candidate for the dietary source of different minerals in the human diet.…”
Section: Discussionsupporting
confidence: 59%
“…Fe and Zn deficiency in particular appears to be a global health issue, affecting the populations of both developed and undeveloped countries [58]. Our finding highlights the nutritional value of G. frondosa which was previously shown to contain high concentrations of starch and total dietary fiber [59]. Although the bioavailability of Ca, Cu, Fe, Mg, Mn, P and Zn in G. frondosa remains to be studied more fully, this species would appear to be a promising candidate for the dietary source of different minerals in the human diet.…”
Section: Discussionsupporting
confidence: 59%
“…These values are higher to those reported by León-Guzman et al (1997) for wild mushrooms collected in Queretaro, Mexico (13.2-17.5 % DW), but in the range of the commercial Italian fresh mushrooms reported by Manzi et al (2001Manzi et al ( , 2004. Portabella (26.2 % DW) and commercial champignon (33.73% DW) showed lower protein content than those reported by Dikeman et al (2005) for the same mushrooms (42.4 and 37.5 %, respectively). However, the mushrooms studied by Dikeman et al (2005) presented lower moisture content which affects directly protein content.…”
Section: Proximate Compositioncontrasting
confidence: 64%
“…Portabella (26.2 % DW) and commercial champignon (33.73% DW) showed lower protein content than those reported by Dikeman et al (2005) for the same mushrooms (42.4 and 37.5 %, respectively). However, the mushrooms studied by Dikeman et al (2005) presented lower moisture content which affects directly protein content.…”
Section: Proximate Compositioncontrasting
confidence: 60%
“…Scientific explorations of Shiitake mushrooms such as Lentinus edodes, Maitake mushrooms such as Grifola frondosa, chanterelles such as Chaterellus carius, white button mushrooms such as Agaricus bisporus, and oyster mushrooms have shown that they serve as repositories of B-vitamins such as niacin, flavin and pyridoxine (Solomko and Eliseeva, 1988); organic acids such as ascorbate, shikimate, malate and fumarate; carbohydrates such as the -glucans; monoterpenoid and diterpenoid lipids; proteins such as hydrophobins and trace elements such as selenium (Dikeman et al, 2005;Valentao et al, 2005). These substances have been found through several in vitro and in vivo studies to be responsible for the antimicrobial, antioxidant, antitumor, antihypertensive and antiaging potentials of edible mush-*Corresponding author.…”
Section: Introductionmentioning
confidence: 99%